faint sausage encodes a novel extracellular protein of the immunoglobulin superfamily required for cell migration and the establishment of normal axonal pathways in the Drosophila nervous system. - Lekven, A.C.; Tepass, U.; Keshmeshian, M.; Hartenstein, V. (Development, 1998)
We examined the structure of the nervous system in Drosophila embryos homozygous for a null mutation in the faint sausage (fas) gene. In the peripheral nervous system (PNS) of fas mutants, neurons fail to delaminate from the ectodermal epithelium; in the central nervous system (CNS), the positions of neuronal cell bodies and glial cells are abnormal and normal axonal pathways do not form. Sequence analysis of fas cDNAs revealed that the fas protein product has characteristics of an extracellular protein and that it is a novel member of the immunoglobulin (Ig) superfamily. In situ hybridization demonstrated that fas transcripts are expressed throughout the embryo but they are in relatively high concentrations in the lateral ectoderm, from which the peripheral nervous system delaminates and in the CNS. Antiserum directed against Fas protein was found to stain neurons but not glia in the CNS. We conclude that fas encodes a protein that, in the developing nervous system, is present on the surface of neurons and is essential for nerve cell migration and the establishment of axonal pathways.